Effects of preoperative serum lactate dehydrogenase levels on long-term prognosis in elderly patients with hepatocellular carcinoma undergoing transcatheter arterial chemoembolization - Gan, Yuantao; Gao, Fengwei; Du, Bo; Liu, Yu; Xue, Qian; Fu, Jinqiang (Frontiers in Surgery, 2022)
Objective To analyze the effects of preoperative serum lactate dehydrogenase (LDH) levels on the long-term prognosis in elderly patients with hepatocellular carcinoma undergoing transcatheter arterial chemoembolization. Methods 106 elderly patients with hepatocellular carcinoma undergoing transcatheter arterial chemoembolization were selected in our hospital, including 57 cases of preoperative serum LDH levels ≤ 400 U/L as the treatment group, and 49 cases of LDH levels > 400 U/L as the control group, and the long-term prognosis were compared between the two groups. Results After one day, there was no significant difference in serum LDH levels between the two groups (P>0.05). After 7 days, 1 week, 1, 6 and 12 months, the serum LDH levels of the two groups were lower than one day after operation (P all<0.05), and those levels in the treatment group were lower than those of the control group (P all<0.05). 3 years after the operation, the serum LDH levels of the two groups were lower than one day after operation (P both<0.05), but there was no significant difference between the two groups (P>0.05). The rate of significant efficacy in the treatment group was higher than that in the control group after 1 years (P<0.05). The significant efficiency and effective rate of the patients with the levels of serum LDH decreased were higher than those serum LDH levels increased after operation for 3 years (P<0.05). Conclusion The detection of the levels of serum LDH before operation can help to evaluate the long-term prognosis of elderly patients with hepatocellular carcinoma undergoing transcatheter arterial chemoembolization, so it can provide some strategies to select more appropriate and effective solutions for the clinical treatment.